English Teachers’ Instructional Practices as Determinants to Students’ 21st Century Skills - Ragay , Groselie; Futalan, Maria Chona (Journal of Interdisciplinary Perspectives, 2024)
The study aimed to examine how the instructional methods employed by English teachers and the overall academic performance of students contribute to the development of 21st-century skills The research involved 277 students from public senior high schools in Bais City. It utilized a descriptive-correlational approach, using a validated questionnaire for data collection, and applied statistical methods including mean, weighted mean, and Multiple Linear Regression Analysis for data analysis. The study revealed that the extent of teachers’ instructional practices in terms of drills, contextualization, mediated learning, technology in the classroom, visualization, cooperative learning, and inquiry-based learning is “high.” It was also found that the students’ 21st-century skills in terms of problem-solving, information literacy, and critical thinking are classified as “high.” Moreover, the visualization and inquiry-based learning practices of the teachers were found to be significant predictors of the students’ problem-solving skills. In addition, the results indicated that contextualization, use of technology in class, visualization, and cooperative learning are determinants of students’ information literacy skills. Lastly, the findings signified that the use of technology in class and cooperative learning significantly predict students’ critical thinking skills.